An energy and carbon footprint assessment upon the usage of hemp-lime concrete and recycled-PET façades for office facilities in France and Italy. (1st January 2018) - Maalouf, Chadi; Ingrao, Carlo; Scrucca, Flavio; Moussa, Tala; Bourdot, Alexandra; Tricase, Caterina; Presciutti, Andrea; Asdrubali, Francesco
Abstract: Energy efficiency and the reduction of greenhouse gas emissions are actual key issues in all the economic sectors and, in particular, in buildings which is acknowledged worldwide as one of the most energy-consuming. In this context, it would be desirable to duly address those issues by searching for and assessing proper solutions and strategies: the usage of eco-friendly construction materials can be considered as one of those. This paper reports upon the performance of three façades containing sustainable products that are manufactured using natural resources and, alternatively, post-consumer waste based materials; those are: hemp-concrete; and Recycled PolyEthylene Terephthalate (R-PET), respectively. The energy performance of each façade was assessed in terms of cooling and heating demands, electrical consumptions and indoor thermal comfort including indoor temperature and relative humidity. Additionally, a Carbon Footprint (CF) assessment was carried out considering both the estimated energy demands and the life-cycle emission factors associated with the energy mix of the countries where the façades were located, i.e. France and Italy. Based upon the findings of the study, the R-PET façade represented the most performing solution between the three façades in all the scenarios considered and, moreover, the humidity-sensitive flow rate ventilation system came out as a solution able to reduce the electricity consumptions. Finally, considering the Carbon Footprint results, the energy country mix emerged as a key issue, making the Italian case study the worst one, though the total electrical energy consumption were comparable with those of the other case studies.